Processo de institucionalização da reforma do ensino médio: análise das disputas envolvidas na configuração final da Lei nº 13.415/2017 no Congresso Nacional - Sperandio, Renan dos Santos (2019)
The present study aims to analyze the role of the main subjects, discourses and interests that participated in the elaboration and approval of the high school reform, originated in MP Nº 746/2016, and defined in Law Nº 13.415/2017 during the Temer government. Through a documentary-based investigation, based on information available on the National Congress website, this paper analyzed the legislative process of the High School Reform, covering the initial disputes about the necessity and relevance of the reform, analyzing the Explanatory Memorandum, publication of MP Nº 746/16, public hearings, the clashes surrounding the amendments and Law Nº 13.415/2017 that instituted the "New High School". From this analysis it was possible to identify the partisan groups, as well as parliamentarians, interests and speeches that represent sectors of society that express a perspective of education of young people for the country, which occurs during a deep crisis of capital and democracy. For the academic production published between the years 2016 and 2017 by authors of the critical field of education the reform of High School is a threat to the universal right of young Brazilians to attend the final stage of basic education. Such a change, in addition to serving business, reactionary, and managerial interests, should increase the social and educational gap among students of different social classes. In the legislative political debate it is evident that while for some, the Middle School is an important stage for the integral formation of the man, while being generic, that needs a training that embraces the totality of knowledge, and a knowledge that makes possible its emancipation, for others the project of High School should be linked to the interests of training to market to the interests of the training market. Training for entrepreneurship and the simple work provided by the reform further links the poorest young people to the scenario of economic uncertainty and the emptying of the State's role in education.